Pendekatan Project Based Learning (PJBL) untuk Meningkatkan Keterlibatan Siswa dan Prestasi Belajar pada Mata Pelajaran Sejarah Kelas X di SMA Swasta Kartika 1-4 Pematangsiantar - Harahap, Rika Rahmadhani (Medan Resource Center, 2023)
The research explores the utilization of project-based learning approaches in teaching history to tenth-grade students at Kartika 1-4 Pematangsiantar Private High School. Forty students participated in the study, with the objective of assessing the impact of this approach on academic performance and engagement levels. Various data collection instruments, such as observation sheets, interviews, written exams, field notes, and student worksheets, were employed in this two-cycle classroom action research. Study results suggest that integrating project-based learning models into history learning can positively impact student engagement and academic performance. The increase in students' grades in each cycle corroborates these findings. In cycle I, research success criteria that emphasize students' active participation in physical, mental and social aspects in the learning process are met in 75% of cases. Student learning outcomes are scored 75 on a scale of 1 to 100. When the project-based learning paradigm was implemented, student participation increased significantly, with an average score of 80% and a rise from 67% to 92% between cycles. Furthermore, each learning outcome's average score rose from 72.5% in cycle I to 95% in cycle II, with an 83.8% categorization level. These findings imply that the use of project-based learning approaches can enhance students' academic achievement and encourage ongoing learning.